2013
DOI: 10.1177/0013916513488784
|View full text |Cite
|
Sign up to set email alerts
|

Using Public Transport Can Make Up for Flying Abroad on Holiday

Abstract: Compensatory Green Beliefs (CGBs) refer to beliefs that the negative effects of energy-inefficient or unsustainable behaviors (e.g., flying abroad on holiday) can be compensated for by engaging in energy-efficient or sustainable practices (e.g., using public transport). The present research developed and validated a scale to measure endorsement of CGBs. This scale formed part of an online survey, which investigated the relationship between endorsement of CGBs and how people think and behave in relation to ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 40 publications
(47 reference statements)
4
68
0
2
Order By: Relevance
“…Existing results, however, suggest that even an ad-hoc similarity based on whether a given behavior belongs conceptually to one subdomain or another translates into an endorsement of compensatory statements. Table 1 displays items from the Green Compensatory Behaviors Scale developed by Kaklamanou et al (2013). They are ordered from the least endorsed to the most endorsed by study participants, as reported by its authors.…”
Section: Similarity Of Behaviorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Existing results, however, suggest that even an ad-hoc similarity based on whether a given behavior belongs conceptually to one subdomain or another translates into an endorsement of compensatory statements. Table 1 displays items from the Green Compensatory Behaviors Scale developed by Kaklamanou et al (2013). They are ordered from the least endorsed to the most endorsed by study participants, as reported by its authors.…”
Section: Similarity Of Behaviorsmentioning
confidence: 99%
“…One of the strategies that people often apply to neutralize negative feelings in such a situation is formulating compensatory beliefs. Compensatory beliefs are convictions that the harmful effects of people's behaviors may be compensated for by engaging in other activities (Kaklamanou, Jones, Webb, & Walker, 2013). For example, someone who buys an SUV believes that the harmful effects of exhaust gases may be neutralized by using public transportation on weekends.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, because of the lower per kilometre operating costs of the new vehicle, the consumer uses the car more, which lessens the net benefit of the switch (or in some cases ends up with a net detriment). Research being conducted by myself and others is seeking to clarify the mechanisms that might feed into this effect, in order to hopefully reduce its impact [2,3].…”
Section: A View From the Countrymentioning
confidence: 99%